National law applicable to stock market operations - García-Pita y Lastres, José Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Commercial Law was born impregnated with internationality and, although for a time it lost that condition, it later had to recover it, since the rupture of the original internationality of Commercial Law coincided with a subsequent reactivation of international commercial traffic, together with the preponderance of the countries economically more powerful. The resurgence of a flourishing and active international economic traffic, based on the “recognition of human interdependence”, confronts merchants and entrepreneurs, States and the public of consumers and investors with several important Lastresphenomena: on the one hand, with the phenomenon of so-called multinational companies, and -on the other hand- with the phenomenon of international contracting. Well then; If the characteristic of Law as a system of norms is that it concerns people, precisely in the context of their social relations and if that context is defined in terms of place and time, we must also include in the material scope of validity of this affirmation the Stock Market and Securities Market Law, which - equally - must be concerned with issues such as the scope and situation of the markets, and with rules or principles such as the “locus regit actum” and “tempus regit actum”, or the “lex loci delicti”, or the “forum rei” and the “forum rei sitae”, etc., given that the growing globalization of financial markets is manifested in the internationalization of operations on negotiable securities and financial instruments.The recognition of the freedom of capital movement which brings with it “the admission to offi-cial listing on the stock exchanges of the Member States of securities issued by [foreign] companies”, constitutes an “important modality of access to these capital markets” of other countries. So; taking into account the evident internationality of the operations of capital markets and Securities Market Law, it is obvious that a good part of its sources will be of an international nature, either because they are rules of international treaty law, or because the complexity which is typical of the relationships that are establis-hed in commercial law in all its branches and - specifically - stock market and securities markets Law, determines the need for private international law to come into play and - more precisely - the Conflict law, so that, as a consequence of the application of a conflict rule, the determination of the applicability of a specific national law has occurred.
Keywords: Stock exchange; stock market; conflict of laws; conflict rules; contract/enterprise link; “lex bursae”